PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP EFEKTIVITAS KERJA PEGAWAI PADA DINAS KESEHATAN KABUPATEN PURWAKARTA - Abdul Haris Munandar (Magister Manajemen Pascasarjana Universitas Langlangbuana, 2021)
This study aims to determine the effect of motivation and work environment on the effectiveness of employees at the Health Office of Purwakarta Regency, West Java. The method used is a survey method. Respondents as many as 40 people were selected randomly (Proportionate Stratified Random Sampling). The instrument uses a questionnaire to collect data on motivation variables, work environment and employee work effectiveness. Data analysis used simple correlation technique, multiple correlation, and multiple regression technique. The results of the study: first, there is an influence of motivation with employee work effectiveness. This means that the higher the employee's motivation, the better the employee's work effectiveness. Vice versa, the lower the employee's motivation, the lower the effectiveness of the employee's work. Second, there is the influence of the work environment on the effectiveness of employees' work. This means that the better the work environment, the better the effectiveness of the employee's work. Vice versa, the less the work environment, the less effective the employee's work. Third, there is the influence of motivation and work environment on the effectiveness of employees' work. It means that the higher the employee's motivation and the better the work environment, the better the employee's work effectiveness. On the other hand, the lower the employee's motivation and the lower the work environment, the less effective the employee's work will be.